Pengaruh Jumlah Buah dan Jenis Kemasan terhadap Sifat Fisik, Kimia, dan Masa Simpan Buah Tomat (Lycopersicum esculentum Mill.) - IDA BAGUS GEDE UPADANA MANUABA; ANAK AGUNG GEDE SUGIARTA; I NYOMAN GEDE ASTAWA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2022)
Effect of Number of Fruits and Type of Packaging on Physical, Chemical Properties and Shelf Life of Tomato Fruit (Lycopersicum esculentum Mill.) The demand for tomatoes increases along with the increase in economic growth and population. Efforts to maintain the quality of tomatoes are to delay ripening using various plastic packaging. This study aims to determine the effect of the right amount of fruit in the packaging and determine the suitable packaging in maintaining the physical, chemical and shelf life of tomatoes. The research was carried out from December 2020 to January 2021 at the Plant Breeding and Seed Laboratory, Faculty of Agriculture, Udayana University, Jl. PB. Sudirman, Denpasar. The experimental design used was a factorial completely randomized design (CRD) with 4 replications and 2 treatment factors so that 24 experimental units were obtained. The 2 treatment factors were as follows: packaging treatment (K) consisted of three treatments K0 = Control (without packaging), K1 = Polypropylene (PP) packaging, K2 = Polyethylene (PE) packaging and number of fruit (T) consisted of two treatments T1 = 3 pieces in a pack, T2 = 4 pieces in a pack. The results showed that the use of polypropylene packaging (K1) and the use of 3 packaged pieces (T1) were able to extend the shelf life of up to 22.75 days, compared to the polyethylene packaging type (K2). The smallest weight loss was found in the treatment of polypropylene packaging type (K1) at 4 Hsp which reached 0.05%. Treatment of the type of polypropylene packaging (K1) showed a low respiration rate at 4 Hsp which reached 22.88 mg CO2/kg/hour. The treatment of polypropylene packaging type (K1) showed the highest hardness level at 4 Hsp, namely 8.40 mm/100/gram/second. The results showed that the number of fruits per package had an effect on weight loss, respiration rate, and shelf life of tomatoes.